Context and Challenges of Service Delivery in Local Government: Insights of the Service Providers from Pokhara, Nepal - Wagle, Prakash (Journal of Development and Social Engineering, 2025)
The People's Movements in 1990 and 2006 have brought significant changes in the political system in Nepal. Among the various spheres of change, the autonomous approach in local government has unlocked innovative prospects for service delivery to the general public. Nevertheless, local service delivery is still questionable in addressing the intensified expectations of the people. In this regard, this study explores the insights of service providers regarding the context and limitations on local service delivery at Pokhara Metropolitan City, Nepal. The study adopts an exploratory research design and a qualitative research approach to obtain research aims and objectives. The study utilises qualitative data through in-depth interviews from 12 service providers from different Wards in Pokhara Metropolitan City. The findings reveal that the effectiveness of local government is significantly constrained by several factors. The most prominent challenge identified is the lack of adequate cooperation and coordination among the three tiers of government, which restricts local autonomy and governance. Furthermore, the study identifies a lack of sufficient and efficient human resources, budget and infrastructure limitations, and limited public awareness and participation as other challenges in service delivery at the local level. Despite the complexity of these obstacles, the study concludes with an optimistic outlook, observing the progress in service delivery mechanisms following the implementation of federalism in Nepal.